2021
DOI: 10.3390/ijerph18083865
|View full text |Cite
|
Sign up to set email alerts
|

Traumatized Syrian Refugees with Ambiguous Loss: Predictors of Mental Distress

Abstract: Refugees from war zones often have missing significant others. A loss without confirmation is described as an ambiguous loss. This physical absence with simultaneous mental persistence can be accompanied by economic, social or legal problems, boundary ambiguity (i.e., uncertainty about who belongs to the family system), and can have a negative impact on mental health. The aim of this study was to identify sociodemographic and loss-related predictors for prolonged grief, anxiety, depression, post-traumatic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…Several studies have found elevated prolonged grief disorder (PGD) symptom levels in conflict-affected and refugee groups with disappeared loved ones [ 9 , 10 , 11 ]. PGD is characterized by severe grief symptoms (e.g., intense yearning or emotional pain, avoidance of loss-related reminders) causing distress and impairments in daily life for an extended period after the death of a loved person [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have found elevated prolonged grief disorder (PGD) symptom levels in conflict-affected and refugee groups with disappeared loved ones [ 9 , 10 , 11 ]. PGD is characterized by severe grief symptoms (e.g., intense yearning or emotional pain, avoidance of loss-related reminders) causing distress and impairments in daily life for an extended period after the death of a loved person [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has identified violent and potentially traumatic losses as being among the strongest risk factors for the development of PGD [ 13 ]. Therefore, it is not surprising that persons with ambiguous loss have an increased risk of developing PGD symptoms, but also other stress-related symptoms such as posttraumatic stress disorder or depression [ 9 , 11 ]; for systematic reviews, see [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, resettling in a new country can provoke various post‐migration stressors. These include a challenging accommodation situation, poor socio‐economic conditions, uncertainty, fear of detention, experiences of discrimination, language difficulties, social isolation, or complications in the asylum‐application process and feelings of ambiguous loss (Böttche et al, 2016; Liedl et al, 2016; Porter & Haslam, 2005; Priebe et al, 2016; Renner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%